Psychodynamic day treatment programme for patients with schizophrenia spectrum disorders: Dynamics and predictors of therapeutic change. (13th September 2017) - Pec, Ondrej; Bob, Petr; Pec, Jan; Hrubcova, Adela
Abstract : Objectives: The purpose of this study was to test whether a psychodynamically based group psychotherapeutic programme might improve symptoms, social functions, or quality of life in patients with schizophrenia spectrum disorders and to investigate factors that might predict clinical improvement or dropouts from the programme. Design: A quantitative prospective cohort study. Methods: We have investigated 81 patients with schizophrenia spectrum disorders who participated in a 9‐month psychodynamically based psychotherapeutic day programme. The patients were assessed at the beginning and end of the programme, and then at 1‐year follow‐up. The assessment included psychotic manifestations (HoNOS), quality of life (WHOQOL‐BREF), demographic data, and daily doses of medication. 21 patients dropped out from the programme, and 46 patients succeeded in undergoing follow‐up assessment. Results: The psychotic manifestations (self‐rating version of HoNOS) and quality of life measured with WHOQOL‐BREF (domains of social relationships and environment) were significantly improved at the end of the programme and at follow‐up. However, the manifestations on the version for external evaluators of HoNOS were improved only at follow‐up. Years of psychiatric treatment, number of hospitalizations or suicide attempts, and experience of relationships with a partner were negatively related to clinical improvement, whereas symptom severity, current working, or study activities were related positively. Conclusions: The results show that a group psychodynamic programme may improve the clinical status and quality of life of patients with schizophrenia spectrum disorders. This type of programme is more beneficial for patients with higher pre‐treatment symptom severity and the presence of working or study activities. Practitioner points: A psychodynamically based group programme improves the clinical status and quality of life in patients with schizophrenia spectrum disorders. Data indicate that changes on the subjective level are detectable by the end of the programme, while changes on the objective level are detectable at follow‐up assessment. Symptom severity and working or study activities are positively related to the clinical improvement in this type of programme, while a high number of years in psychiatric treatment or psychiatric hospitalizations are negatively related. The doses of medication (antipsychotics or antidepressants) show no significant relationship to clinical improvement.